Biological Control of Plant Disease Caused by Bacteria - Triwidodo Arwiyanto (Jurnal Perlindungan Tanaman Indonesia, 2014)
Bacterial diseases in plants are difficult to control. The emphasis is on preventing the spread of the bacteria rather than curing the diseased plant. Integrated management measures for bacterial plant pathogens should be applied for successfull control. Biological control is one of the control measures viz. through the use of microorganisms to suppress the growth and development of bacterial plant pathogen and ultimately reduce the possibility of disease onset. The study of biological control of bacterial plant pathogen was just began compared with of fungal plant pathogen. The ecological nature of diverse bacterial plant pathogens has led scientists to apply different approach in the investigation of its biological control. The complex process of entrance to its host plant for certain soil-borne bacterial plant pathogens need special techniques and combination of more than one biological control agent. Problem and progress in controlling bacterial plant pathogens biologically will be discussed in more detail in the paper and some commercial products of biological control agents (biopesticides) will be introduced.  Penyakit tumbuhan karena bakteri sulit dikendalikan. Penekanan pengendalian adalah pada pencegahan penyebaran bakteri patogen dan bukan pada penyembuhan tanaman yang sudah sakit. Untuk suksesnya pengendalian bakteri patogen tumbuhan diperlukan cara pengelolaan yang terpadu. Pengendalian secara biologi merupakan salah satu cara pengendalian dengan menggunakan mikroorganisme untuk menekan pertumbuhan dan perkembangan bakteri patogen tumbuhan dengan tujuan akhir menurunkan kemungkinan timbulnya penyakit. Sifat ekologi bakteri patogen tumbuhan yang berbeda-beda mengharuskan pendekatan yang berbeda pula dalam pengendaliannya secara biologi. Masalah dan perkembangan dalam pengendalian bakteri patogen tumbuhan secara biologi didiskusikan secara detail dalam makalah ini.